Identifying Chinese Herbal Medicine Network for Endometriosis: Implications from a Population-Based Database in Taiwan. (27th June 2017) - Tsai, Pei-Ju; Lin, Yi-Hsuan; Chen, Jiun-Liang; Yang, Sien-Hung; Chen, Yu-Chun; Chen, Hsing-Yu
Abstract : Background . Endometriosis is a common but bothersome gynecological disease, and Chinese herbal medicine (CHM) is used for treating endometriosis. The aim of this study is to explore CHM network and core treatments for endometriosis by analyzing nationwide CHM prescription database. Methods . From 1998 to 2013, the CHM prescriptions made primarily for endometriosis among women diagnosed with endometriosis (ICD-9-CM code: 671) by gynecologists during their reproductive age were collected. CHM network analysis was then carried out by using association rule mining and social network analysis. Results . A total of 12, 986 CHM prescriptions made for endometriosis were analyzed. There were 556 kinds of CHM ever used, and, in average, each prescription was composed of 6.2 CHMs. Gui-Zhi-Fu-Ling-Wan (GZFLW) was used most frequently, followed by Cyperus rotundus (28.1% and 18.8% of all prescriptions, resp.) . Additionally, the combination of Cyperus rotundus with GZFLW (8.0%) was the most frequently used combination of two CHMs . CHM network showed that GZFLW was the core CHM for endometriosis and graphically demonstrated the extensive coverage of TCM syndromes and pathogenesis of endometriosis. Conclusions . CHM network provides graphical demonstration and summary of commonly used CHMs for endometriosis, and further studies are warranted based on these findings.